Evaluasi Peresepan Obat Berdasarkan Indikator Peresepan WHO di Apotek M Bandung - Saviola Saviola; Keri Lestari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Rational drug use is one of the essential efforts to improve the quality of pharmaceutical services and ensure patient safety. Evaluation of prescribing patterns can be conducted using prescribing indicators established by the World Health Organization (WHO). This study aimed to describe drug use based on WHO prescribing indicators at Apotek M Bandung during January 2026. The study employed an observational design with retrospective data collection from prescription documents received at the pharmacy. The research sample was determined using a total sampling method in accordance with predefined inclusion and exclusion criteria. The indicators analyzed included the average number of drugs per prescription, the percentage of generic drug prescribing, antibiotic prescribing, injectable drug prescribing, and the use of medicines listed in the National Essential Medicines List (DOEN). The results showed that the average number of drugs per prescription was 2.4 items. The percentage of generic drug prescribing was 84.3%, antibiotic prescribing was 0.5%, and no injectable drugs were prescribed. The percentage of medicines prescribed from the DOEN was 88.20%. Overall, most indicators met WHO standards, except for the average number of drugs per prescription and the use of DOEN medicines, which had not yet reached the ideal values. Based on these findings, it can be concluded that the prescribing pattern at Apotek M Bandung reflects a relatively rational use of medicines; however, further efforts are still required to optimize compliance with WHO prescribing standards